Treatment of Stifle Joint Luxation in a Cat Using a Temporary Trans-Articular Locking Plate - Eid, Chadi; Lusetti, Filippo; Bonardi, Andrea; Martini, Filippo Maria (VCOT Open, 2021)
The aim of this study was to report the surgical treatment of stifle joint luxation through temporary immobilization of the joint with locking plates in a cat. Stifle joint was immobilized using a temporary trans-articular locking plate applied medially. Return to function was assessed by physical and radiographic follow-up examinations. The cat had good return to function despite a reduction in range of motion. Moderate chronic gonarthritis developed, as seen radiographically. Under the limitation of this single case, temporary trans-articular plating may be considered as useful method for the treatment of long-standing, severely displaced stifle joint luxations in cats.
Keywords: cat; stifle; luxation; trans-articular plating